Step
*
of Lemma
page55_witness
∀[U:Type]. ∀[P,Q:U ⟶ ℙ].  ((∀x:U. (P[x] 
⇒ Q[x])) 
⇒ (∀x:U. P[x]) 
⇒ (∀x:U. Q[x]))
BY
{ xxxExtract of Obid: page55
     normalizes to:
     
     λf,g,x. (f x (g x))
     finishing with Autoxxx }
Latex:
Latex:
\mforall{}[U:Type].  \mforall{}[P,Q:U  {}\mrightarrow{}  \mBbbP{}].    ((\mforall{}x:U.  (P[x]  {}\mRightarrow{}  Q[x]))  {}\mRightarrow{}  (\mforall{}x:U.  P[x])  {}\mRightarrow{}  (\mforall{}x:U.  Q[x]))
By
Latex:
xxxExtract  of  Obid:  page55
      normalizes  to:
     
      \mlambda{}f,g,x.  (f  x  (g  x))
      finishing  with  Autoxxx
Home
Index